Numerical Analysis on Behavior of Reinforced Concrete T-Beam with Shear Strengthening using U-Strap Steel Plates and Bolts - I Ketut Sudarsana, Ida Bagus Rai Widiarsa, I Gede Gegiranang Wiryadi, Putu Chandra Sajana (International Journal of Advanced Science and Technology, 2020)
Beams in a reinforced concrete building may suffer shear deficiency due to increasing the loads or mistaken in construction. This paper presents the analysis results of a T-beam with shear strengthening using U-strap steel plates and bolts. Modeling and analysis were done in a finite element software ABAQUS/CAE 2016. The behavior of concrete at plastic conditions were modeled using Concrete Damage Plasticity (CDP) features that require to calibrate its main parameters to match the results of an experimental T-beam. The best CDP’s validated parameters that give very close results with the behavior of tested specimens are a dilation angel (y ) of 55˚ and eccentricity (ɛ) of 0.1. The mesh size is 30mm. The friction coefficient of the steel plate and bolts to the concrete surface is 0.1 and 0.42, respectively. The results show that the CDP feature in ABAQUS is able to predict accurately the experimental behavior of the T-beam. The numerical results in terms of midspan deflection and maximum loads are about 98.84% and 100.05% of the experimental results, respectively. Concrete micro-cracks in the experimental specimen which result in stiffness’ degradation on the specimen are not considered in the numerical analysis so that a stiffer deflection response is obtained at the initial loading stage. It is also found that increasing the u-strap steel plate thickness and width can improve the beam shear capacity. However, enlarging the U-strap steel plate spacing reduces the beam shear capacity